"Falling values": artifacts or source of unique information? Drastically low electrical conductivity of acupuncture points is accompanied by significant deviations of EEG, HRV, immunity, metabolism and GDV parameters - Anatoliy Gozhenko; Toto Zantaraia; Walery Zukow (Nicolaus Copernicus University in Toruń, 2024)
Background. With this article, we start the project "Functional relationships between the parameters of acupuncture points and the neuro-endocrine-immune network", thereby joining the construction of a bridge between the Western and Eastern paradigms of medicine. Materials and methods. The object of observation were 10 women (32-76 years) and 10 men (37-67 years) examined twice with a weekly interval. The volunteers were considered practically healthy, but the initial testing revealed deviations from the norm in a number of parameters of the neuro-endocrine-immune (NEI) network as a manifestation of maladaptation. We recorded electrical conductivity in acupuncture points (AP) Pg(ND), TR(X) and MC(AVL) as well as parameters of NEI network, gas discharge visualization (GDV) and metabolism. Results. The preliminary analysis of the parameters revealed in the female SO drastic deviations from both the reference and the average for the sample, the levels of electrical conductivity of three pairs of AP - that is, the so-called "falling values", which are usually removed from the subsequent analysis as artifacts. However, we found the same drastic or significant deviations of a number of other parameters of GDV, EEG, HRV, adaptation hormones, immunity and metabolism in this patient. Therefore, the registered drastic decrease in electrical conductivity of AP is by no means an artifact, but reflects the peculiarities of the NEI network, GDV and metabolism of the patient's body during the first examination. It is significant that upon re-examination, the deviations of the parameters significantly or completely approached the range of the average for the sample ± SD or the norm ± SD. Conclusion. The above gives us a reason to initiate a broad discussion of the problem of "falling variables" as carriers of unique information that is ignored and lost.